The effect of phosphorylcoline-coated cardiopulmonary by-pass circuits on morbidity and mortality in patients with congenital open cardiac surgery - Bolat, Alı; Surer, Suleyman; Gülbahar, Özlem; Bolat, Esef; Gultekın, Yıldırım; Kutsal, Alı (My University, 2021)
Objective: Our aim in this study is to investigate the relationship between mortality and morbidity of phosphorylcholinecoated oxygenator circuit used in heart-lung machine in congenital open-heart surgery operations.Material and Method: The study was conducted in Dr. Sami Ulus Child Diseases Training and Research Hospital CardiovascularSurgery Clinic between 2008-2009. 30 congenital heart patients were included. The patients were divided into 2 groups of 15people. In one of the groups, a phosphorylcholine coated oxygenator circuit was used in the heart lung machine (GroupP). In the other group, a standard oxygenator circuit was used (Group C).Congenital heart surgery was performed for 19ventricular septal defects (VSD), 5 secundum atrial septal defects (ASD), 3 primum ASD, 2 mitral insufficiency and 1 discretsubaortic membrane. Extubation times, intensive care and discharge times, 24-hour drainage follow-up, inotropic drug use,blood and fresh frozen plasma (FFP) transfusion amount, aspartate aminotransferase, alanine aminotransferase, creatinephosphokinase-MB, urea, blood urea nitrogen, creatinine, white cell number of platelets, lactate dehydrogenase, albumin, totalprotein, C-reactive protein, prothrombin time, partial thromboplastin time, fibrinogen, D-dimer, C5a and elastase levels werecompared perioperatively.Results: In the study, it was determined that the discharge time was shorter in Group P. It was found that the increase ind-dimer values with fibrinogen was less in Group P. These were found to be statistically significant (p<0.05). There was nosignificant difference between groups in other parameters (p>0.05). There was no mortality in either group.Conclusion: In this study, phosphorylcholine-coated oxygenator did not significantly reduce the inflammatory responseduring cardiopulmonary by-pass (CPB). There was no difference between the two groups in terms of morbitidity and mortality.However, the fact that fibrinogen values, which are the acute phase reactants, are lower than the control group and the increasein d-dimer values remain limited may be important in terms of hemocompatibility of the phosphorylcholine coated circuit.
Keywords: Mühendislik; Biyotıp; Tıbbi Araştırmalar Deneysel; Kalp ve Kalp Damar Sistemi